Search for contact interactions in deep inelastic e+p → e+X scattering at HERA - Breitweg, J; Chekanov, S; Derrick, M; Krakauer, D; Magill, S; Musgrave, B; Pellegrino, A; Repond, J; Stanek, R; Yoshida, R; Mattingly, M; Abbiendi, G; et al. (2000)
In a search for signatures of physics processes beyond the Standard Model, various eeqq vector contact-interaction hypotheses have been tested using the high-Q2 deep inelastic neutral-current e+p scattering data collected with the ZEUS detector at HERA. The data correspond to an integrated luminosity of 47.7pb-1 of e+p interactions at 300 GeV center-of-mass energy. No significant evidence of a contact-interaction signal has been found. Limits at the 95% confidence level are set on the contact-interaction amplitudes. The effective mass scales Λ corresponding to these limits range from 1.7 TeV to 5 TeV for the contact-interaction scenarios considered.